Development of functional oral health literacy assessment instruments: Application of literacy and cognitive theories. (9th September 2013) - Bridges, Susan M.; Parthasarathy, Divya S.; Au, Terry K.F.; Wong, Hai Ming; Yiu, Cynthia K.Y.; McGrath, Colman P.
Abstract Objectives This paper describes the development of a new literacy assessment instrument, the Hong Kong Oral Health Literacy Assessment Task for Paediatric Dentistry (HKOHLAT‐P). Its relationship to literacy theory is analyzed to establish content and face validity. Implications for construct validity are examined by analyzing cognitive demand to determine how "comprehension" is measured. Methods Key influences from literacy assessment were identified to analyze item development. Cognitive demand was analyzed using an established taxonomy. Results The HKOHLAT‐P focuses on the functional domain of health literacy assessment. Items had strong content and face validity reflecting established principles from modern literacy theory. Inclusion of new text types signified relevant developments in the area of new literacies. Analysis of cognitive demand indicated that this instrument assesses the "comprehension" domain, specifically the areas of factual and procedural knowledge, with some assessment of conceptual knowledge. Metacognitive knowledge was not assessed. Conclusions Comprehension tasks assessing patient health literacy predominantly examine functional health literacy at the lower levels of comprehension. Item development is influenced by the fields of situated and authentic literacy. Inclusion of content regarding multiliteracies is suggested for further research. Development of functional health literacy assessment instruments requires careful consideration of the clinical context in determining construct validity.